Retraction: Differential endocytosis and signaling dynamics of insulin receptor variants IR-A and IR-B - Giudice, Jimena (2012)
The authors wish to retract this paper after it has come to their attention that the constructs of insulin receptor (IR) isoform A were of isoform B. This was discovered when the constructs were subcloned into retroviral vectors to be used in a different study. Thus the significant differences reported between IR-A and IR-B must be assumed to be erroneous and, in agreement with the Journal of Cell Science editorial policies, the paper must be retracted. A detailed comparison between certified IR-A and IR-B is being conducted and will be reported.